2012
DOI: 10.1021/ja302743g
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Encapsulation of Nucleic Acids Using an Engineered Nonviral Protein Capsid

Abstract: In Nature, protein capsids function as molecular containers for a wide variety of molecular cargoes. Such containers have great potential for applications in nanotechnology, which often require encapsulation of non-native guest molecules. Charge complementarity represents a potentially powerful strategy for engineering novel encapsulation systems. In an effort to explore the generality of this approach, we engineered a nonviral, 60-subunit capsid, lumazine synthase from Aquifex aeolicus (AaLS), to act as a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…In addition, Hilvert and coworkers reported that engineered nonviral protein capsids such as lumazine synthase from Aquifex aeolicus are also applicable as nano-carriers for proteins and DNA. [14][15][16] Currently, however, functional modification of natural protein capsules, such as plant viral capsids and virus-like lumazine synthase capsids, requires complicated technologies such as gene recombination and protein expression. Therefore, the reconstruction of virus-like nanocapsules from synthetic molecules would enhance their potential for molecular designs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hilvert and coworkers reported that engineered nonviral protein capsids such as lumazine synthase from Aquifex aeolicus are also applicable as nano-carriers for proteins and DNA. [14][15][16] Currently, however, functional modification of natural protein capsules, such as plant viral capsids and virus-like lumazine synthase capsids, requires complicated technologies such as gene recombination and protein expression. Therefore, the reconstruction of virus-like nanocapsules from synthetic molecules would enhance their potential for molecular designs.…”
Section: Introductionmentioning
confidence: 99%
“…In the nearly 40 years since the first high-resolution structure of an icosahedral virus 11 , the structures and functions of a wide array of viral capsids have been characterized. This has inspired efforts to reengineer naturally occurring protein containers 12 and to design new polypeptides 13 to package biological molecules. In one case, lumazine synthase—a naturally occurring, non-viral protein container—was evolved in E. coli to sequester a toxic protein 14 .…”
mentioning
confidence: 99%
“…Inspired by this, various classes of viral‐mimicking biohybrid NPs have been introduced for genome delivery . Understanding the structure of viruses inspired many efforts to engineer protein containers and to synthesize nucleic acid‐encapsulating polypeptides . It has recently been shown that protein assemblies could be re‐engineered to encapsulate their own genome .…”
Section: Challenges and Limitations For In Vivo Delivery Of Npsmentioning
confidence: 99%